EXPRESSIVE AND COMMUNIKATIVE IDIOMS OF MODERN GERMAN AS A TRANSLATION PHENOMENON - Hordii, О. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article deals with the translation of the expressive and communicative phraseology. The methods of translating of these units are analyzed on the material of the literary works of the German writers of the 20th century. Investigated idioms are defined as units with a pronounced national-cultural specificity, making it difficult to search for translation equivalents. The necessity of inclusion of these units in the formation of linguistic and cultural competence of an interpreter is argued.